Pemberdayaan Perempuan dalam Upaya Pencegahan Kehamilan di Luar Nikah di Desa Jangga Kecamatan Batin XXIV Kabupaten Batanghari - Fitri Utami; Ayu Mustika Handayani (Jurnal Akademika Baiturrahim Jambi, 2023)
Pregnancy out of wedlock contains very complicated and complex problems for teenagers, especially for those who are directly involved in it. One of the prevention of pregnancy outside of marriage is by providing health education through empowering women. This study aims to determine the empowerment of women in an effort to prevent pregnancy out of wedlock. This research is a quantitative research with a pre-experimental method with a pre-post test design. The research population was all young women in Jangga Village, Batin XXIV District, Batanghari Regency, totaling 34 people with a sampling technique that was a total sampling of 34 people. The research instrument used a questionnaire sheet and analyzed univariate and bivariate using the T-test. The results showed that there was an influence of women's empowerment in preventing pregnancy outside of marriage in Jangga Village, Batin XXIV District, Batanghari Regency in 2022 with a p-value of 0.000. Empowerment of women can increase the knowledge of adolescents regarding the prevention of pregnancy outside of marriage.